Old but New: Group IIA Phospholipase A2 as a Modulator of Gut Microbiota - Yoshitaka Taketomi; Yoshimi Miki; Makoto Murakami (Metabolites, 2022)
Among the phospholipase A2 (PLA2) superfamily, the secreted PLA2 (sPLA2) family contains 11 mammalian isoforms that exhibit unique tissue or cellular distributions and enzymatic properties. Current studies using sPLA2-deficient or -overexpressed mouse strains, along with mass spectrometric lipidomics to determine sPLA2-driven lipid pathways, have revealed the diverse pathophysiological roles of sPLA2s in various biological events. In general, individual sPLA2s exert their specific functions within tissue microenvironments, where they are intrinsically expressed through hydrolysis of extracellular phospholipids. Recent studies have uncovered a new aspect of group IIA sPLA2 (sPLA2-IIA), a prototypic sPLA2 with the oldest research history among the mammalian PLA2s, as a modulator of the gut microbiota. In the intestine, Paneth cell-derived sPLA2-IIA acts as an antimicrobial protein to shape the gut microbiota, thereby secondarily affecting inflammation, allergy, and cancer in proximal and distal tissues. Knockout of intestinal sPLA2-IIA in BALB/c mice leads to alterations in skin cancer, psoriasis, and anaphylaxis, while overexpression of sPLA2-IIA in Pla2g2a-null C57BL/6 mice induces systemic inflammation and exacerbates arthritis. These phenotypes are associated with notable changes in gut microbiota and fecal metabolites, are variable in different animal facilities, and are abrogated after antibiotic treatment, co-housing, or fecal transfer. These studies open a new mechanistic action of this old sPLA2 and add the sPLA2 family to the growing list of endogenous factors capable of affecting the microbe–host interaction and thereby systemic homeostasis and diseases.